Implikasi Yuridis Perkawinan Campuran Siri terhadap Kedudukan Hukum Anak - Mia Afrian; Eti Yusnita; Sri Asmita (AHKAM, 2026)
Unregistered mixed marriages conducted in siri form remain prevalent in societal practice and give rise to serious legal issues, particularly regarding the legal status of children born from such unions. The absence of marriage registration means that such marriages do not obtain administrative legal recognition and directly affects the child’s legal status. This study aims to analyze the juridical implications of perkawinan campuran siri (unregistered mixed marriages) for the legal status of the child and to examine legal remedies to secure a lawful status for the child under Indonesian positive law. The research employs a normative legal method with a statutory approach and descriptive-analytical analysis of provisions governing marriage registration, child status, and civil legal relations. The findings show that mixed marriages performed siri lack administrative legal force, thereby creating uncertainty regarding the child’s legal status and exposing the child to being positioned as an out-of-wedlock child with limited civil relations and legal protection from the state. The study concludes that isbat nikah constitutes an essential legal remedy to confer legal recognition on the parents’ marriage while simultaneously ensuring certainty and protection of the child’s rights. The implications of this study underscore the urgency of marriage registration as a legal instrument for realizing legal certainty and the protection of children within the Indonesian family law system.